Severe metformin intoxication in an adolescent: A case report - Dana Adriana Dascultu; Elena Madalina Petran (Amaltea Medical Publishing House, 2020)
Introduction. The frequency of acute metformin intoxication is increasing with increasing availability and accessibility of children and adolescents to this oral antidiabetic. Acute metformin intoxication can be severe and evolve to multiple organ failure. Case report. A 16-year old teenager is transfered from another hospital to the Toxicology and Intensive Care unit of "Grigore Alexandrescu" Emergency Hospital for Children, in Bucharest, for somnolence and vomiting after she has voluntarily taken 10 tablets of Siofor (Metformin). Laboratory findings on admission detected the presence of metabolic acidosis (pH =7.28, EB = -9.4mmol/l, HCO3 = 14.2 mmol/l, lactate = 4.06 mg/dl), and kidney function testes revelead an increased value of creatinine 1.57 mg/dl. Initial treatment included sodium bicarbonate and endovenous glucose and electrolytes without improvment in the clinical status of the patient who evolved with severe lactic acidosis (pH = 7.19, lactate = 5.5 mg/dl, HCO3 = 18 mmo/l), acute renal failure (urea = 59 mg/dl, creatinine = 4.06 mg/dl). She was transfered to the nephrology unit of another hospital to perform emergency hemodialysis. The patient subsequently underwenth two hemodialysis session, following dialysis normal renal function and full recovery was obtained. Conclusions. Acute metformin poisoning can be severe and lead to death if unrecognized, monitored and treated rapidly. Lactic acidosis imposes rapid and effective suportive treatment measures or renal replacement therapy